APLIKASI BUDIDAYA TANAMAN SAYUR DAN BUAH SERTA DAMPAKNYA TERHADAP KONSUMSI SAYUR DAN BUAH PADA SISWA SDN 1 PANDAK DAN SDN 1 SUMAMPIR KABUPATEN BANYUMAS - Sapto Nugroho Hadi; Kartini Kartini; Tri Harjoso (LP2M Universitas Hasanuddin, 2019)
Abstract. This activity aims to carry out the application of organic vegetable and fruit cultivation in SDN 1 Pandak and SDN 1 Sumampir, Banyumas Regency, Central Java Province and find the impact on the level of consumption of vegetables and fruit. The target audiences are the fifth-grade students of SDN 1 Pandak, Baturraden District and SDN 1 Sumampir, North Purwokerto District, Banyumas Regency. The activity was carried out for ten months with several methods such as organic vegetable and fruit cultivation training from seeding, planting, to harvesting. The vegetable and fruit products from further cultivation were processed into food products made from vegetables and fruits. These various food products were served to students to be enjoyed together. The researcher then observed the impact of the activity from the pre-test and post-test answers. The results showed that the application activities of vegetable and fruit cultivation organically in both partner schools can be carried out properly. The vegetable and fruit products were successfully harvested and served in the form of processed food. This activity has an impact on increasing the frequency of consumption of vegetable and fruit. The frequency of frequent consumption of vegetable in SDN 1 Pandak increased from 65.79% to 89.47%, while in SDN 1 Sumampir increased from 96.15% to 98.08%. The frequency of fruit consumption frequency in SDN 1 Pandak increased from 81.58% to 97.37%, while in SDN 1 Sumampir increased from 57.69% to 86.54%.Keywords: Vegetable and fruit cultivation, SDN 1 Pandak, SDN 1 SumampirAbstrak. Kegiatan ini bertujuan untuk melakukan aplikasi budidaya tanaman sayur dan buah secara organik pada SDN 1 Pandak dan SDN 1 Sumampir, Kabupaten Banyumas dan mengetahui dampaknya terhadap tingkat konsumsi sayur dan buah. Khalayak sasaran adalah Siswa Kelas V SDN 1 Pandak, Kecamatan Baturraden, Kabupaten Banyumas dan SDN 1 Sumampir, Kecamatan Purwokerto Utara, Kabupaten Banyumas. Kegiatan dilakukan selama sepuluh bulan dengan metode yang dilakukan berupa pelatihan budidaya tanaman sayur dan buah secara organik, dari mulai penyemaian, penanaman, sampai pemanenan. Produk sayur dan buah hasil budidaya lebih lanjut diolah menjadi produk makanan berbahan sayur dan buah. Aneka produk makanan ini disajikan kepada siswa untuk dapat dinikmati bersama. Dampak kegiatan diamati secara seksama melalui jawaban pre-test dan post-test. Hasil menunjukkan kegiatan aplikasi budidaya tanaman sayur dan buah secara organik pada kedua sekolah mitra dapat dilaksanakan dengan baik. Produk tanaman sayur dan buah berhasil dipanen dan disajikan dalam bentuk makanan olahan berbahan/berkomposisi sayur dan buah. Kegiatan ini berdampak kepada peningkatan frekuensi konsumsi sayur dan buah. Frekuensi tingkat keseringan konsumsi sayur di SDN 1 Pandak meningkat dari 65,79% menjadi 89,47%, sedangkan di SDN 1 Sumampir meningkat dari 96,15% menjadi 98,08%. Frekuensi tingkat keseringan konsumsi buah di SDN 1 Pandak meningkat dari 81,58% menjadi 97,37%, sedangkan di SDN 1 Sumampir meningkat dari 57,69% menjadi 86,54%.Kata Kunci: Budidaya tanaman sayur-buah, SDN 1 Pandak, SDN 1 Sumampir